Assessment of cryogenic energy storage systems efficiency - E. V. Blagin; D. A. Uglanov (Вестник Самарского университета: Аэрокосмическая техника, технологии и машиностроение, 2025)
This study evaluates the efficiency of cryogenic energy storage systems from energy, exergy, and economic perspectives. Cryogenic energy storage systems that store energy through gas liquefaction and regasification, offer high energy capacity but face challenges in storage efficiency. The authors propose a comprehensive performance indicator that integrates these factors, addressing limitations of traditional metrics like the round-trip efficiency, which fails to account for external heat/cold sources. Analysis of 30 installations reveals that systems utilizing compression heat and cryogenic cold achieve up to 70% efficiency, while those relying solely on electricity average 25%. Key findings highlight the trade-offs between energy density, cost, and thermodynamic perfection, with advanced configurations (e.g., hybrid systems with LNG cold recovery) achieving round-trip efficiency more than 100% but lower exergy efficiency (10.4%). A novel composite metric balances , exergy efficiency, and specific energy capacity, identifying optimal designs. The study concludes that integrating auxiliary heat/cold storage and external energy sources (e.g., geothermal, LNG) enhances performance, though practical constraints like regenerative heat exchanger stability persist.